Directors’ remuneration disclosure transparency in Nigeria and the influence of block share ownership - Odewale, Robert W.; Kamardin, Hasnah (Maryland Institute of Research (MIR), 2015)
This paper examines directors’ remuneration disclosure transparency in an emerging economy (Nigeria).We specifically examine how the block share ownership influences the level of transparency in the disclosure of directors’ remuneration in a sample of companies listed on the Nigerian Stock Exchange in 2012. Using ordinary least squares and binary logistic regressions to examine the relationship, we find that block share ownership is associated with lower transparent disclosure of directors’ remuneration.The result shows a positive relationship between audit quality and transparent disclosure of directors’ remuneration. The study finds that the transparency score is less than 40%.On the whole, we provide evidence that managers in Nigerian Listed Companies are inclined not to make voluntary disclosure of their remuneration to the public.This paper has implication for policy makers and regulatory authorities in Nigeria on the need to embark on remuneration disclosures reforms so as to make directors’ remuneration disclosure mandatory for Nigerian Listed Companies to make it comparable with accepted global good practice.This study contributes to the remuneration disclosure transparency literature by providing support for the expropriation hypothesis in the behaviour of block shareholders from an emerging economy whose market is very much different from those of developed economies.